2022
DOI: 10.3390/nano12111868
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal and Antiviral Bionic Metalized Nanocoatings

Abstract: In diverse living organisms, bionanocoatings provide multiple functionalities, to the surfaces they cover. We have, previously, identified the molecular mechanisms of Turing-based self-assembly of insect corneal nanocoatings and developed forward-engineering approaches to construct multifunctional soft bionic nanocoatings, encompassing the Drosophila protein Retinin. Here, we expand the versatility of the bionic nanocoatings, by identifying and using diverse Retinin-like proteins and different methods of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
(95 reference statements)
0
8
0
Order By: Relevance
“…Arthropods possess diverse types of anti-re ective corneal nanocoatings, represented, in addition to the nipple arrays, by parallel strands, maze-like structures, irregularly spaced protrusions, dimples, and various transitions among them 7,10,11,21,22 . In our ongoing exploration of the diversity of insect corneal nanocoatings, we here assessed 97 species of the order Coleoptera (beetles, Supplementary Table S1).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations

Evolutionary bet-hedging at the nanoscale

Kryuchkov,
Jobin,
Savitsky
et al. 2024
Preprint
Self Cite
“…Arthropods possess diverse types of anti-re ective corneal nanocoatings, represented, in addition to the nipple arrays, by parallel strands, maze-like structures, irregularly spaced protrusions, dimples, and various transitions among them 7,10,11,21,22 . In our ongoing exploration of the diversity of insect corneal nanocoatings, we here assessed 97 species of the order Coleoptera (beetles, Supplementary Table S1).…”
Section: Introductionmentioning
confidence: 99%
“…While genome sequencing and assembly of some re ies are in process 37 , Luciola and Lampyris genomes have not yet been sequenced. This prevented us from a direct assessment of the corneal proteome and identi cation of the Turing Activator candidates -the approach we have previously applied to several insects with sequenced genomes 8,11,21 . However, earlier we showed that admixing of waxes (Turing Inhibitor) and Drosophila Retinin (Turing Activator) on glass surfaces recapitulates diverse insect-like nanocoatings such as nipples-like, maze-like and dimpled patterns, with different light-and liquid-handing functionalities 8,11 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations

Evolutionary bet-hedging at the nanoscale

Kryuchkov,
Jobin,
Savitsky
et al. 2024
Preprint
Self Cite